COVID-19 broken access: implications for individuals with substance use disorders. Issue 8 (17th November 2022) - Estreet, Anthony T.; Archibald, Paul; Price, Len
ABSTRACT: The impact of the COVID-19 (coronavirus) pandemic created a paradigm shift in the delivery of substance abuse treatment services. Still, it also provided an opportunity for healthcare workers and professionals, and treatment providers to adjust, problem-solve, and meet these challenges head-on. The pandemic led practitioners and healthcare professionals to change how they deliver treatment options but still ensuring that their clients received access to adequate and effective clinical services. It is suggested that during the ongoing COVID‐19 pandemic, healthcare professionals should make every effort to ensure accessibility and availability of substance abuse treatment services through critical actions. This paper will address the physical health implications, as well as the trauma-stress related effects of COVID-19 on individuals with substance use disorders (SUD). In all, this article will identify barriers to treatment access, accentuate treatment strategies, and provide measures and recommendations for maintaining and improving services for substance-dependent patients.